TEACHERS’ CHALLENGE TO DEVELOP STUDENTS' CREATIVE THINKING SKILLS IN ACROSTIC WRITING POETRY AT ELEMENTARY SCHOOL - Indri Pudjiati; Tuti Tarwiyah Adi; Otib Satibi Hidayat (Universitas Majalengka, 2024)
Children's poetry is a literary problem that is widely studied and in demand, but elementary school students, are constrained in the problem of arranging poetic words, difficulty developing ideas, the impact of lack of guidance in the post-COVID-19 pandemic, or lack of attention in writing poetry. This problem is the background for the improvement of learning after the COVID-19 pandemic carried out by teachers in the form of real action learning to write acrostic poetry in developing creative thinking skills as a form of student-centered learning challenges. This study aims to describe the challenge of teachers to develop students' creative thinking skills in writing acrostic poetry in elementary school. This type of research is qualitative. The research method used is a qualitative descriptive study, with a phenomenological approach. The procedure of this research is an interview and literature study. The source of data in this study came from primary data and secondary data. The findings of this study are 1) School Profile; 2) creative thinking skills; 3) learning to write acrostic poetry; and 4) teacher challenges. The results showed that in the face of challenges in learning to write acrostic poetry in elementary school, teachers need to develop models, approaches, strategies, methods, and techniques of learning to write acrostic poetry centered on students so that the ability to write poetry students in the development of language and literature can continue to be accommodated optimally. This study concludes that learning to write acrostic poetry for students makes an effective and significant contribution to the development of students' creative thinking skills in writing poetry, this is a challenge for teachers in the implementation of concrete actions to improve the quality of student-centered learning.